Asuhan Kebidanan Komunitas Pada Keluarga Tn “N” Dengan Demam Post Partum Hari Ke 6 di Dusun Aik Lengis Desa Kuta Wilayah Kerja Puskesmas Kuta Kecamatan Pujut Kabupaten Lombok Tengah - Eka Rosfyant Yunita; Elly Sustiyani (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
The results of the study of Community Midwifery Care for Mr. "N" Family with Postpartum Fever on Day 6, Dusun Aik Lengis, Kuta Village, Kuta Health Center Working Area, namely the assessment of subjective and objective data on Mrs. "M" postpartum on day 6 with fever, existing subjective and objective data and can identify problems, needs and diagnoses based on information that has been collected from the assessment of Mrs. "M" postpartum on day 6 with fever. Diagnosis or potential problems in accordance with the data obtained from the assessment of Mrs. "M" postpartum on day 6 with fever, collaboration, and referrals to Mrs. "M" postpartum on day 6 with fever, interventions on Mrs. "M" postpartum on day 6 with fever, care needed by Mrs. "M" postpartum on day 6 with fever. Students have conducted an evaluation in accordance with the actions that have been given to Mrs. "M" postpartum on day 6 with fever obtained from verbal responses, nonverbal responses, and examination results. Not all problems can be identified due to time constraints for the author to provide midwifery care to clients who have not fully recovered.